2014
DOI: 10.1111/pim.12084
|View full text |Cite
|
Sign up to set email alerts
|

Immune responses to Schistosoma haematobium infection

Abstract: Urogenital schistosomiasis is one of the greatest single infectious sources of human morbidity and mortality known. Through a complex cycle of infection, migration and eventual maturation and mating, S. haematobium (the aetiological agent of urogenital schistosomiasis) deposits highly immunogenic eggs within the bladder and other pelvic organs, activating a wide range of immune programs that determine both infection outcome as well as downstream immunopathology. In this review, we discuss the experimental and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 98 publications
1
25
0
Order By: Relevance
“…The present study reported different proportions of AEs comparable to those found in other studies involving praziquantel and / or albendazole. However, there are variations that may occur due to the heterogeneous antecedents of the participating individuals, such as age, nutritional and immunological status, socioeconomic conditions, environmental exposure, prevalence and intensity of infection, stage of parasite development, etc [13,18,20,21,[31][32][33][34][35][36][37]. Zwang et al reviewed the efficacy and safety of PZQ (40mg/kg), and report that the main AEs experienced and their incidences are mainly abdominal pain (31.8%), muscle pain (29.2%), joint pain (20.2%), headache (13.6%), diarrhoea (12.9%), fatigue (9.6%), nausea (10.6%), dizziness (11.9%), vomiting (7.9%) and itching (9.8%) [18].…”
Section: Discussionmentioning
confidence: 99%
“…The present study reported different proportions of AEs comparable to those found in other studies involving praziquantel and / or albendazole. However, there are variations that may occur due to the heterogeneous antecedents of the participating individuals, such as age, nutritional and immunological status, socioeconomic conditions, environmental exposure, prevalence and intensity of infection, stage of parasite development, etc [13,18,20,21,[31][32][33][34][35][36][37]. Zwang et al reviewed the efficacy and safety of PZQ (40mg/kg), and report that the main AEs experienced and their incidences are mainly abdominal pain (31.8%), muscle pain (29.2%), joint pain (20.2%), headache (13.6%), diarrhoea (12.9%), fatigue (9.6%), nausea (10.6%), dizziness (11.9%), vomiting (7.9%) and itching (9.8%) [18].…”
Section: Discussionmentioning
confidence: 99%
“…The trematode Schistosoma haematobium ( S. haematobium ) is an exemplary case of parasite-induced inflammation and cancer, specifically bladder SCC (BSCC) (Odegaard and Hsieh, 2014). Following S. haematobium infection of the urinary tract, primary tumors usually develop in the bladder wall, within the fibrotic granuloma tissue that forms around the parasitic eggs (Odegaard and Hsieh, 2014).…”
Section: Etiology Of Sccsmentioning
confidence: 99%
“…Following S. haematobium infection of the urinary tract, primary tumors usually develop in the bladder wall, within the fibrotic granuloma tissue that forms around the parasitic eggs (Odegaard and Hsieh, 2014). Chronic inflammation is thought to cause metaplasia of the transitional urothelium into squamous tissue before an accumulation of oncogenic mutations that culminate in uncontrolled cell growth.…”
Section: Etiology Of Sccsmentioning
confidence: 99%
“…In longitudinal studies, antibody responses to specific schistosome antigens have been shown to correlate with resistance to reinfection . Generally, the antibody responses associated with human resistance to reinfection are directed against the schistosome adult worm and not egg antigens . This finding may not be surprising as the immune responses to crude adult worm and egg antigens have been widely studied.…”
Section: Discussionmentioning
confidence: 99%
“…60,61 Generally, the antibody responses associated with human resistance to reinfection are directed against the schistosome adult worm and not egg antigens. 62 This finding may not be surprising as the immune responses to crude adult worm and egg antigens have been widely studied. However, limited work has shown that IgG 32 and IgE 31 antibody responses to larval antigens are associated with resistance to reinfection.…”
Section: Discussionmentioning
confidence: 99%